2022
DOI: 10.1111/aor.14170
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous infusion of liposome‐encapsulated hemoglobin (HbV) acutely prevents hemorrhagic anemia‐induced lethal arrhythmias, and its efficacy persists with preventing proarrhythmic side effects in the subacute phase of severe hemodilution model

Abstract: Background: Artificial oxygen carriers (HbV) can treat hemorrhagic shock with lethal arrhythmias (VT/VF). No reports exist on subacute HbV's effects.Methods: Acute and subacute resuscitation effects with anti-arrhythmogenesis of HbV were studied in 85% blood exchange rat model (85%-Model). Lethal 85%-Model was created by bone marrow transfusion and femoral artery bleeding in 80 SD rats in HbV-administered group (HbV-group), washed erythrocyte-administered group (wRBC-group), and 5% albumin-administered group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…HbV, due to its smaller size, is better than red blood cells for reperfusion into the capillaries of the graft and helps to oxygenate the graft tissue . Recent studies have shown that liposome-encapsulated hemoglobin can improve the arrhythmia in rabbit obstetric hemorrhage and severe fatal hemorrhage models . HbV-based oxygen carriers can also be used as organ supports, stabilizing the circulation of pneumonectomy rats with hemorrhagic shock .…”
Section: Hb-based Oxygen Carriersmentioning
confidence: 99%
“…HbV, due to its smaller size, is better than red blood cells for reperfusion into the capillaries of the graft and helps to oxygenate the graft tissue . Recent studies have shown that liposome-encapsulated hemoglobin can improve the arrhythmia in rabbit obstetric hemorrhage and severe fatal hemorrhage models . HbV-based oxygen carriers can also be used as organ supports, stabilizing the circulation of pneumonectomy rats with hemorrhagic shock .…”
Section: Hb-based Oxygen Carriersmentioning
confidence: 99%